Zmiany zapisów kanonów w obszarze materialnego prawa małżeńskiego na mocy motu proprio „De concordia inter Codices” - Dzierżon, Ginter (Ius Matrimoniale, 2017)
The major focus of attention of the author of the article was the question of the changes in the text of canons in the area of material marital law based on motu proprio „De concordia inter Codices” issued on 31st May 2016 by Pope Francis. The conclusions of the author drawn from his thorough analysis of the content of this papal document are as follows: firstly, the clarification included in art. 11 DCIC puts an end to doctrinal discussions concerning the possibility of a deacon assisting in giving marriage to Eastern faithfuls; secondly, the modification of the content of can. 1109 CIC (art. 7 DCIC) results from the ambiguity of the term “ritus” functioning in Western legislation - the author believes that accentuating the legal-institutional meaning of the notion corresponds with terminological changes introduced in art. 1-2 DCIC, while, on the other hand, it is consistent with the terminology included in canons 29-30 CCEO; thirdly, the new hypothesis included in art. 10 DCIC related to the extraordinary form of entering into marriage widens the range of competence of a Catholic ordinary of a place. This is because the legislator, taking into account ecumenistic considerations, wishes to meet the spiritual needs of Eastern non-Catholics who found themselves in an unusual situation.